Glomerular Immune Deposition in MPO-ANCA Associated Glomerulonephritis Is Associated With Poor Renal Survival - Lin, Wei; Shen, Chanjuan; Zhong, Yong; Ooi, Joshua D.; Eggenhuizen, Peter; Zhou, Ya-Ou; Luo, Hui; Huang, Jing; Chen, Jin-Biao; Wu, Ting; Meng, Ting; Xiao, Zhou; et al. (Frontiers in Immunology, 2021)
Rapidly progressive glomerulonephritis caused by antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis is typically characterized as pauci-immune glomerulonephritis. However, immune complex (IC) deposition in the glomerulus has been reported in a growing number of studies. Here, we assess the presence of glomerular IC deposits alongside renal outcome in myeloperoxidase (MPO)-ANCA associated glomerulonephritis (MPO-ANCA GN). Clinical and histopathologic characteristics of 97 patients with MPO-ANCA GN classified by renal biopsy were extracted retrospectively from electronic medical records. The extent of immune deposits in the kidney (C3, C4, C1q, IgA, IgG, IgM) at diagnosis were analyzed by immunofluorescence（IF）. Patients were followed up for a median period of 15 months. The response to treatment and outcomes of renal and histological lesion changes were assessed. In our study, 41% (40/97) of patients showed positive IF (≥2+) for at least one of immunoglobulin or complement components tested. Patients with IC deposits showed higher levels of serum creatinine (p=0.025), lower platelet (p=0.009), lower serum complement C3 (sC3) (≤790 ml/L) (p=0.013) and serum IgG (p=0.018) than patients with pauci-immune (PI) deposition at diagnosis. End-stage renal disease was negatively associated with eGFR (p＜0.0001), platelet count (p=0.046) and serum globulin (p=0.001). Patients with lower sC3 levels showed a worse renal outcome than the patients with normal sC3 at diagnosis (p=0.003). Analysis of the components of the renal deposits found that patients with IgG deposits exhibited a poorer renal outcome compared to patients that were IgG negative (p=0.028). Moreover, Bowman's capsule rupture occurred less frequently in patients with IgM deposition compared with IgM negative counterparts (p=0.028). Vascular lesions and granuloma-like lesions had been seen more frequently in cases with IgA deposition than those without deposition (p=0.03 and 0.015, respectively).In conclusion, patients with immune complex deposits in the kidney showed less platelet count, lower sC3 and sIgG levels, and higher serum creatinine levels. Patients with low sC3 at initial and with continued low sC3 during the treatment displayed a trend towards poorer kidney survival. Moreover, the IC group showed a worse renal outcome than the PI group, further enforcing the present strategy of introducing complement targeted therapies in AAV.